Switching cost and deposit demand in China - Chun-Yu Ho (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
This paper develops and estimates a dynamic model of consumer demand for deposits in which banks provide differentiated products and product characteristics that evolve over time. Existing consumers are forward-looking and incur a fixed cost for switching banks, whereas incoming consumers are forward-looking but do not incur any cost for joining a bank. The main finding is that consumers prefer banks with more employees and branches. The switching cost is approximately 0.8% of the deposit's value, which leads the static model to bias the demand estimates. The dynamic model shows that the price elasticity over a long time horizon is substantially larger than the same elasticity over a short time horizon. Counterfactual experiments with a dynamic monopoly show that reducing the switching cost has a comparable competitive effect on bank pricing as a result of reducing the dominant position of the monopoly.
URN:NBN:fi:bof-201408072200
Keywords: G21; L10; 330; banks in China; demand estimation; switching cost